2019
DOI: 10.3390/ijms20246116
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Proteomics and Metabolomics Analysis Provides Insights into Ganoderic Acid Biosynthesis in Response to Methyl Jasmonate in Ganoderma Lucidum

Abstract: Ganoderma lucidum is widely recognized as a medicinal basidiomycete. It was previously reported that the plant hormone methyl jasmonate (MeJA) could induce the biosynthesis of ganoderic acids (GAs), which are the main active ingredients of G. lucidum. However, the regulatory mechanism is still unclear. In this study, integrated proteomics and metabolomics were employed on G. lucidum to globally identify differences in proteins and metabolites under MeJA treatment for 15 min (M15) and 24 h (M24). Our study succ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 47 publications
(69 reference statements)
0
14
0
Order By: Relevance
“…Thus, the genetic foundation of responsiveness to the MeJA signal should have evolved in thymus species. Methyl jasmonate treatment alters the gene expression of many transcription factors as well as protein and metabolic levels [ 54 ]. Terpenoids are the most common and structurally varied category of plant secondary metabolites [ 55 ], according to our findings.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the genetic foundation of responsiveness to the MeJA signal should have evolved in thymus species. Methyl jasmonate treatment alters the gene expression of many transcription factors as well as protein and metabolic levels [ 54 ]. Terpenoids are the most common and structurally varied category of plant secondary metabolites [ 55 ], according to our findings.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, plants are activated in response to abiotic or biotic stresses, such as pathogens. For example, reactive oxygen species (ROS), some pathogenesis-related (PR) proteins and other secondary metabolites are produced and accumulate [ 26 ], whereas MeJA-induced synthesis of PR-proteins and other stress proteins or secondary metabolites improves the resistance of plants, as previously studied in tomato, sweet pepper [ 27 ], peanut [ 28 ], other plants, and even the fungus Ganoderma lucidum [ 29 ]. In this study, the MapMan results also showed that the differentially expressed unigenes were associated with signaling, abiotic stress, proteolysis, PR-proteins, and secondary metabolites ( Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…Jiang et al found that treatment of Ganoderma lucidum with methyl jasmonate (MeJA) for 24 h was the optimal condition to induce the biosynthesis of Ganoderma lucidum . MeJA induction can lead to metabolic rearrangements in Ganoderma lucidum , inhibit its normal glucose metabolism, energy supply, and protein synthesis, and promote cellular secondary metabolic production [ 29 ]. After treatment with tributyltin (TBT), the mycelial morphology of Cunninghamella echinulata changed, the metabolic activity was inhibited, and glycolysis and the TCA cycle were dysregulated.…”
Section: Application Of Metabolomics In the Field Of Fungal Researchmentioning
confidence: 99%